An efficient approach for the synthesis of 5-hydroxy-chromeno[2, 3-b]pyridines under catalyst and solvent free conditions. Issue 17 (11th August 2017) - Gupta, Shruti; Khurana, Jitender M.
Abstract : An efficient and sustainable method has been developed for the synthesis of novel 5-hydroxy-chromeno[2, 3- b ]pyridines by the reaction of 3-formylchromone, aromatic amines and malononitrile under catalyst and solvent-free conditions by simply stirring the components magnetically or by grinding at room temperature. Abstract : An efficient and sustainable method has been developed for the synthesis of novel 5-hydroxy-chromeno[2, 3- b ]pyridines by the reaction of 3-formylchromone, aromatic amines and malononitrile under catalyst and solvent-free conditions by simply stirring the components magnetically or by grinding at room temperature. Excellent yields, environmentally benign reaction conditions and easy workup are the advantages of this protocol. The structures have been established unambiguously.